The Effect of Leverage on Financial Performance with Financial Distress Risk as a Moderating Variable in Oil, Gas, and Coal Sub-sector Companies Listed on the Indonesia Stock Exchange for the 2020–2023 Period - Nesa Delfi Eftasari; Susi Sarumpaet (International Journal of Economics and Management Sciences, 2025)
This study aims to determine the effect of leverage on financial performance and the effect of financial distress risk on the relationship between leverage and financial performance. The population in this study is several oil, gas, & coal sub-sector companies listed on the Indonesia Stock Exchange in 2020, 2021, 2022, and 2023. This study uses secondary data. The sampling technique uses the simple purposive sampling method, resulting in 57 companies as samples for 4 years. This study uses Moderated Regression Analysis as the data analysis technique. The results of the study show that leverage has a negative effect on financial performance, and financial distress risk is able to strengthen the relationship between leverage and financial performance.